Expanded Competencies: Acknowledging a Context for Rural Teaching Skills - Marilyn Kay Johnson; Margaret R. Lowe; Thomas W. Sileo; Cable Starlings; Susan Taylor-Alling (Educational Considerations, 1989)
Teacher trainers cannot afford to ignore the need for a specialized set of competencies in preparing teachers for rural settings.